2019
DOI: 10.1002/ijc.32694
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Newcastle disease virus mediated dendritic cell activation and cross‐priming tumor‐specific immune responses ex vivo

Abstract: We have developed an oncolytic Newcastle disease virus (NDV) that has potent in vitro and in vivo anti‐tumor activities and attenuated pathogenicity in chickens. In this ex vivo study using the same recombinant NDV backbone with GFP transgene (NDV‐GFP, designated as rNDV), we found that rNDV induces maturation of monocyte‐derived immature dendritic cells (iDCs) by both direct and indirect mechanisms, which promote development of antigen‐specific T cell responses. Addition of rNDV directly to iDCs culture induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…The observation that direct infection of DCs by MEDI5395, a possible by-product of therapy, enhanced their function as antigen-presenting cells suggests a further mechanism by which MEDI5395 may impact the priming of antitumor immune T-cell response. A similar DC-maturing effect has been observed using an NDV-GFP virus [32]. Concomitant to this, release of IFN-γ by activated T cells, as observed in vitro here, may upregulate PD-L1 expression within the TME.…”
Section: Discussionsupporting
confidence: 82%
“…The observation that direct infection of DCs by MEDI5395, a possible by-product of therapy, enhanced their function as antigen-presenting cells suggests a further mechanism by which MEDI5395 may impact the priming of antitumor immune T-cell response. A similar DC-maturing effect has been observed using an NDV-GFP virus [32]. Concomitant to this, release of IFN-γ by activated T cells, as observed in vitro here, may upregulate PD-L1 expression within the TME.…”
Section: Discussionsupporting
confidence: 82%
“…Functional maturation of DCs is characterized by decreased antigen capture and efficient antigen presentation ( 22 ). Previous studies in the context of NDV have shown that although the expression of surface markers and cytokines is efficiently enhanced ( 3 , 4 ), DCs may remain non-functional as a consequence of apoptosis ( 5 ). In this study, in vitro results indicated that infective NDV acted as a potent inducer of DC maturation, accompanied by increased expression of MHC-I, MHC-II, CD40, CD80, and CD86 on the cell surface ( Figures 1A–E ), as well as the production of pro-inflammatory cytokines ( Figures 1F–H ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NDV suppresses the innate immune response through V protein-mediated MDA5, phospho-STAT1 and MAVS degradation ( 1 , 2 ). NDV is reported to have distinct influences on dendritic cells (DCs) during the early stage of NDV infection, including activation of the DCs and cross-priming of naïve T cells into tumor-specific T cells ( 3 , 4 ). However, another study indicated that infection with a velogenic NDV strain could stimulate an extrinsic apoptosis pathway in DCs, resulting in inhibition of CD4 + T cell proliferation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, tumor-associated antigens (TAAs) and neoantigens (TANs), which are released by tumor cells, are captured by antigen-presenting cells and are ultimately activated by tumor specific T cells in order to respond to tumor antigens (26,27). Secondly, OVs can promote immunogenic cell death by cell necrosis, immunogenic apoptosis and autophagic cell death (27)(28)(29)(30), subsequently releasing danger-associated molecular patterns (DAMPs), including ATP and high-mobility group box 1 protein (28,31,32). In addition, virus-induced tumor cell death also leads to the release of pathogen-associated molecular patterns (PAMPs), such as nucleic acids, proteins and viral capsid components (33,34).…”
Section: Mechanisms Of Oncolytic Virotherapymentioning
confidence: 99%